Pendampingan Pemanfaatan Limbah Tahu Sebagai Pupuk Organik Cair (Poc) Bagi Masyarakat Kelurahan Kayu Manis - Ade Ayu Oksari; Karmanah; Eha Hasni Wahidani; Linar Humaira; Arifah Qurrotu Aina; Rezky Kevin Adha; Harisma Triana Prandika; Yunus Arifien (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Tofu is a food product that comes from processed products (protein coagulation process) of soybeans. This home-based tofu industry, in its processing, can produce waste, namely solid waste (soybean dregs) and liquid waste. Handling of tofu liquid waste is not only a temporary treatment but needs to be done on an ongoing basis, one of which is by making valuable agricultural products having economic value. The methods for implementing this Community Self-Reliance Activity (KKM) include debriefing, team coordination, training, Liquid Organic Fertilizer (POC) application, mentoring and monitoring. The people involved were UKM Harjasari and KWT Ceria Mandiri Kayu Manis. The results of this activity indicate that community service in the form of assistance in using liquid tofu waste as a POC product can reduce environmental pollution and increase public knowledge about the proper use of natural resources. This can be seen from the increase in general understanding and its application, with an average increase of 62.28%.